Working But Still Dependent: The Hourly Wage of Working Wives and that of their Husbands in Australia, Canada, Hungary, The Netherlands, Czechoslovakia, the Federal Republic of Germany Around 1980 - Henk Jan Dirven (Luxembourg Income Study (LIS), 1990)
This paper examines (1) the associations between the hourly wages of two-earners, (2) the association between their educational levels, (3) the extent to which the former association can be explained from the latter together with the effect of education on hourly wage for each spouse separately, and (4) whether the hourly wage o the spouse is influenced by the education level of the other spouse.
Keywords: 330